Apelin has inhibitory effect of endothelium-independent relaxation in the human internal mammary artery - Kacar, Emine; Burma, Oktay; Serhatlioglu, Ihsan; Ulker, Nazife; Yardimci, Ahmet; Uysal, Ayhan; Kelestimur, Haluk (My University, 2019)
Aim: Apelin has important effects on the circulatory system and heart. The main aim of this study was to investigate the effects of apelin-13 on the contraction induced by norepinephrine (NE), and the endothelium-independent relaxation induced by sodium nitroprusside (SNP) in human internal mammary artery (IMA) obtained from patients undergoing coronary artery bypass grafting (CABG) surgery. Material and Methods: IMA rings, obtained from patients undergoing CABG surgery, were suspended in isolated tissue baths containing Krebs-Henseleit solution, which were continuously gassed with 95% O2 and 5% CO2 at 37°C. Results: The IMA rings were pre-contracted with increasing concentrations of norepinephrine (NE 10-9–10-4 mol/l) and the endothelium-independent relaxation responses to sodium nitroprusside (SNP) were studied. Apelin-13 (10 ?M) caused a dosedependent relaxation in NE pre-contracted IMA rings. Apelin also facilitated the endothelium-independent relaxation induced by SNP. Conclusion: According to the results, apelin facilitated the endothelium-independent relaxation and inhibited the contractile activity of IMA. These results suggest that apelin may be a physiological agent against the deterioration of vascular elasticity caused by endothelial damage especially in atherosclerotic cardiac patients and hypertensive patients.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Apelin; Nitroprusside; Internal mammary artery; Coronary artery bypass